1997
DOI: 10.1111/j.1745-6592.1997.tb01270.x
|View full text |Cite
|
Sign up to set email alerts
|

Remediating Ground Water with Zero‐Valent Metals: Chemical Considerations in Barrier Design

Abstract: To gain perspective and insight into the performance of permeable reactive barriers containing granular iron metal, it is useful to compare the degradation kinetics of individual chlorinated solvents over a range of operating conditions. Pseudo first‐order disappearance rate constants normalized to iron surface area concentration (kSA) recently have been reported for this purpose. This paper presents the results of further exploratory data analysis showing the extent to which variation in kSA is due to initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
83
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 13 publications
2
83
0
Order By: Relevance
“…It has been typically observed that zero valent iron degradation of [ Gillham and O'Hannesin, 1994;ET1 Ref. : 3 1054.10;SRT-ESS-96-365;Tratnyek, et. al., 1997; EPA/600/F-97/008; O'Hannesin and Gillham, 19981 Approximately 10 percent of the carbon tetrachloride (CT) mass appears in solution as the intermediate degradation product chloroform (TCM).…”
Section: Zero Valent Iron Enhanced Abiotic Degradation Overvienmentioning
confidence: 99%
“…It has been typically observed that zero valent iron degradation of [ Gillham and O'Hannesin, 1994;ET1 Ref. : 3 1054.10;SRT-ESS-96-365;Tratnyek, et. al., 1997; EPA/600/F-97/008; O'Hannesin and Gillham, 19981 Approximately 10 percent of the carbon tetrachloride (CT) mass appears in solution as the intermediate degradation product chloroform (TCM).…”
Section: Zero Valent Iron Enhanced Abiotic Degradation Overvienmentioning
confidence: 99%
“…Thus, we can see from the Table 1 that benzene has the most potential to desorption from the bed surface with highest vapor pressure and lowest soil-air portion co-efficient. The VOCs reduction could be occurred by several reduction pathways on the coated beds in presence of Fe 0 and Cu 2 O (Lai et al, 2014;Tratnyek et al, 1997) (Fig. 4).…”
Section: Results and Discussion Elimination Of The Btxsmentioning
confidence: 99%
“…Reductive destruction of chlorinated solvents in water has been a very active research area since Gillham and O'Hannesin [2] showed that metallic iron filings could be utilized in passive groundwater remediation schemes [2][3][4][5][6]. In this process, the zerovalent iron serves as an electron donor to reductively dechlorinate the halocarbons to their nonchlorinated analogs and chloride ions.…”
Section: Introductionmentioning
confidence: 99%